Modeling favorable conditions in the downstream of a dam under seismic effects - Hudaykulov Savet; Hudayberdiev Nizomiddin; Kayumov Dilshod; Jurayev Ulugbek (BIO Web of Conferences)
The study presents a comprehensive modeling approach to investigate the favorable conditions in the lower pool of a dam, particularly under seismic impacts. It emphasizes the critical issue of uneven flow distribution along the spillway front, which becomes exacerbated during seismic events. Such uneven flow not only leads to oscillatory movements but also triggers vortex processes that can undermine the structural integrity of the dam. These hydrodynamic phenomena create unfavorable conditions in the lower pool, resulting in the potential for severe erosion that compromises the dam’s operational and safety parameters. To address these challenges, the research utilizes a numerical solution implemented through the finite difference method, focusing on calculating the relative velocity within the apron of the dam. By identifying and quantifying adverse flow patterns, the study aims to inform the development of remedial measures, including channel fastenings and reinforcements, ensuring the resilience and stability of the dam under seismic loads. This investigation is crucial for enhancing dam safety and performance in seismic-prone areas.